Creatures of Darkness : Raymond Chandler, Detective Fiction, and Film Noir - Phillips, Gene D. (Book collections on Project MUSE., 2000)
More than any other writer, Raymond Chandler (1888-1959) is responsible for raising detective stories from the level of pulp fiction to literature. Chandler's hard-boiled private eye Philip Marlowe set the standard for rough, brooding heroes who managed to maintain a strong sense of moral conviction despite a cruel and indifferent world. Chandler's seven novels, including The Big Sleep (1939) and The Long Goodbye (1953), with their pessimism and grim realism, had a direct influence on the emergence of film noir. Chandler worked to give his crime novels the flavor of his adopted city, Los Angel.